A scheduling algorithm for optimizing video traffic - Jiarui DING; Kai LIU; Jie SUN; Zhimin LIU (Dianxin kexue)
Real-time is an important criterion for evaluation of the real-time video traffic. Most of the existing scheduling algorithms have a wide distribution of user time delay. Firstly，based on the analysis of the existing scheduling algorithms and system rate，an algorithm called MT-LWDF was proposed. Secondly，obtained the range of β after the theoretical analysis，the optimal value of β was got by computer simulation. Then，β was set with the optimal value，the simulation relating to average delay of the system，maximum delay of the users，rate of the system，video frame loss rate and other performance was done. And the results indicate that MT-LWDF algorithm can reduce the distribution of user delay at the same time of optimizing the rate of the system.